1999
DOI: 10.1086/302454
|View full text |Cite
|
Sign up to set email alerts
|

The Gene for Cherubism Maps to Chromosome 4p16.3

Abstract: Cherubism is a rare familial disease of childhood characterized by proliferative lesions within the mandible and maxilla that lead to prominence of the lower face and an appearance reminiscent of the cherubs portrayed in Renaissance art. Resolution of these bony abnormalities is often observed after puberty. Many cases are inherited in an autosomal dominant fashion, although several cases without a family history have been reported. Using two families with clinically, radiologically, and/or histologically prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(88 citation statements)
references
References 33 publications
2
76
0
1
Order By: Relevance
“…Small vessels may show perivascular collagen cuffing. Osteoid and bone tissue formation were often seen at the periphery of the lesion tissue, results that have also been observed by Katz and Underhill, 15 Hitomi et al, 22 and Mangion et al 11 Southgate and coworkers 3 established that multinucleated cells in the cherubism are osteoclasts since they synthesized tartrateresistant acid phosphatase, expressed vitronectin receptors, promoted bone resorption at culture and the multinucleated giant cells were inhibited by calcitonin in situ. Treatment of cherubism has not been standardized, making it difficult to indicate a treatment protocol.…”
Section: -13supporting
confidence: 57%
“…Small vessels may show perivascular collagen cuffing. Osteoid and bone tissue formation were often seen at the periphery of the lesion tissue, results that have also been observed by Katz and Underhill, 15 Hitomi et al, 22 and Mangion et al 11 Southgate and coworkers 3 established that multinucleated cells in the cherubism are osteoclasts since they synthesized tartrateresistant acid phosphatase, expressed vitronectin receptors, promoted bone resorption at culture and the multinucleated giant cells were inhibited by calcitonin in situ. Treatment of cherubism has not been standardized, making it difficult to indicate a treatment protocol.…”
Section: -13supporting
confidence: 57%
“…SOX9 has been proposed to be necessary for chondrocyte survival and hypertrophy to delay terminal maturation (Cowan et al 2003, Hattori et al 2010. Furthermore, SOX9 can inhibit the expression of RUNX2, a runt-domain transcription factor, and induce the degradation of RUNX2 in chondrocytes (Mangion et al 1999, Amizuka et al 2000. RUNX2 plays a pivotal role in the promotion of chondrocyte hypertrophy.…”
Section: Introduction On Growth Plate Developmentmentioning
confidence: 99%
“…[7][8][9][10] Now, both hereditary and sporadic cases have been reported and recent genetic studies have shown it to be a separate entity at the molecular level. 11,12 The gene for cherubism has been mapped to seven mutations in the gene encoding SH3-binding protein SH3BP2 on chromosome 4p16.3 that cause cherubism. 10,11 The children affected with cherubism do not usually show mental or physical deformities, but when cherubism is associated with other syndromes like Noonan-like syndrome, 13,14 Ramon syndrome, 15 fragile X syndrome, mental and physical deformities may be seen.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The gene for cherubism has been mapped to seven mutations in the gene encoding SH3-binding protein SH3BP2 on chromosome 4p16.3 that cause cherubism. 10,11 The children affected with cherubism do not usually show mental or physical deformities, but when cherubism is associated with other syndromes like Noonan-like syndrome, 13,14 Ramon syndrome, 15 fragile X syndrome, mental and physical deformities may be seen. 16 Grading of cherubism based on the location of the jaw lesions have been described by Seward and Hankey 17 as follows:…”
Section: Discussionmentioning
confidence: 99%